MODELLING OF A PORTABLE WIND-POWERED ELECTRICITY GENERATION FOR SHRIMP POND IN KALANGANYAR VILLAGE - Maulana, Muhamad Andy; Wrahatnolo, Tri (Departemen Teknik Elektro, Universitas Diponegoro, 2025)
Currently, power generation for pond operations still relies predominantly on gasoline or diesel powered generators. Shrimp pond areas exhibit significant wind energy potential due to their favorable geographic location.This study investigates the utilization of abundant wind energy by modeling a portable wind turbine system to achieve optimal electrical energy generation. Data collected include generator voltage, generator current, rotational speed (rpm), and wind speed. Experimental evaluation comprised two methods: no-load testing and load testing, conducted over a three-day period with measurements taken daily between 10:00 and 16:00. The portable wind power system was successfully tested and implemented. Under no-load conditions, the generator achieved a maximum average voltage of 30.25 V at 1,392 rpm under a wind speed of 3.16 m/s. Under load conditions, it produced a maximum average voltage of 12.31 V and a current of 0.18 A at 432 rpm with a wind speed of 2.08 m/s. Future developments should focus on increasing generator capacity, optimized blade design, and optimizing the portable wind power system compactness to facilitate easier installation and maintenance.